Effects of microcrystalline cellulose on some performance properties of chitosan aerogels - Ozen, Ertan; Yildirim, Nadir; Dalkilic, Berk; E. Ergun, Mehmet (Maderas. Ciencia y Tecnología, 2021)
The aim of this research was to investigate the effect of the microcrystalline cellulose reinforcement on some physical, mechanical, thermal, and morphological properties of the chitosan aerogels. The bio-based chitosan aerogels were produced using chitosan as a matrix and the microcrystalline cellulose as a reinforce material through freeze-drying method. The aerogel suspensions were prepared in five different ratios to investigate the effect of microcrystalline cellulose content. The density, porosity, thermogravimetric analysis, and compressive resistance tests were conducted according to relevant standards. Morphological properties were investigated using scanning electron microscope. The introduction of microcrystalline cellulose significantly improved the compressive resistance, thermal properties (Tonset and T%50) of the chitosan aerogels. The optimum performance properties determined as 0,12 MPa for compressive resistance, 0,27 MPa for compressive modulus, 292,45 °C for Tonset and 365 °C for T%50. According to scanning electron microscope images, aerogels showed microporous structure as expected. As a result, the bio-based chitosan aerogels reinforced with microcrystalline cellulose were successfully manufactured. The mechanical and thermal properties including compressive resistance, compressive modulus, Tonset and T%50 of chitosan- microcrystalline cellulose aerogels found promising.